One Of Each - Mary Ann Hoverman (USA Scholastic Inc, 1997)
Oliver Tolliver lives all alone and has one of everything in his little house-one table, one chair, one apple, and one pear. To him, it's perfect. But when he invites Peggoty Small over to admire his arrangement, he finds she has quite another opinion. She feels his one-of-each house leaves no room for anyone else! Suddenly Oliver sees she's right, and he finds a pair for every single thing in his house. In the end he realizes that sharing makes room for friends. As only she can, Mary Ann Hoberman deftly crafts a simple, comforting story that speaks to every child's experience. Accompanied by Marjorie Priceman's bold, colorful illustrations, this picture book is destined to become a story time favorite.
Keywords: math - MB - Sharing -- math - MB - Sharing